Correlation Between Maternal Emotion Regulation and Husband Support on Early Breastfeeding Initiation Success Rates - Nurul Hidayah; Eva Fauziah; Risca Praharasti (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2025)
Early Breastfeeding Initiation (EBI) is an important step to improve infant health and survival. This study aims to determine the correlation between maternal emotion regulation and husband support on the success of EBI. This study used a quantitative cross-sectional design with a sample of 30 postpartum mothers selected through purposive sampling. The research was conducted in June 2025. The instruments used were tested for validity and reliability, namely the Emotion Regulation Questionnaire (ERQ) and the Postpartum Partner Support Scale (PPSS). Data were analyzed using the chi-square test. The results showed that most mothers had low emotion regulation (40%) and moderate husband support (56.7%). A total of 53.3% of mothers successfully performed EBI. There was a significant correlation between maternal emotion regulation (p = 0.003) and husband support (p = 0.036) with the success of EBI. Maternal emotion regulation and husband support play an important role in supporting the success of EBI.